The First-Principles Investigation of Structural Stability, Mechanical, Vibrational, Thermodynamic, and Optical Properties of CaHfS3 for Optoelectronic Application - Mulugetta Kassa; Nebiyu Debelo; Menberu Woldemariam (Advances in Condensed Matter Physics)
In this study, the structural, electronic, elastic, phonon vibration, thermodynamic features, and optical properties of the orthorhombic phase of (space group Pnma) CaHfS3 were examined by first-principles calculations utilizing the plane wave ultrasoft pseudopotentials in generalized gradient approximations (GGAs) and with Hubbard on-site correction (DFT + U). To improve the value of the band gap, the exchange correlation potential is also approximated with Hubbard correction (GGA + U). The equilibrium state properties such as lattice parameters, unit cell volume, bulk modulus, and its derivative were calculated and are in good agreement with the existing data. The mechanical properties such as bulk modulus, shear modulus, Young’s modulus, and elastic anisotropy were determined from the obtained elastic constants. The ratio of bulk modulus to shear modulus confirms that the orthorhombic phase of CaHfS3 is a ductile material. In addition, the longitudinal sound velocity, transverse sound velocity, and Debye temperature for CaHfS3 have been computed. The absence of negative frequencies in the phonon dispersion curve and the phonon density of states confirm that CaHfS3 in the orthorhombic phase is dynamically stable. The thermodynamic parameters such as free energy, entropy, and heat capacity were examined with variations in temperature. Finally, the absorption coefficient, dielectric constant, energy loss function, reflectivity, and refractive index are discussed in detail in the spectral range 0–1.6 Ry (21.77 eV). The polarizations along (100), (010), and (001) directions significantly show different optical responses.